2010
DOI: 10.1111/j.1468-1331.2010.03105.x
|View full text |Cite
|
Sign up to set email alerts
|

In‐hospital stroke: a multi‐centre prospective registry

Abstract: cardioembolic IS was the most frequent subtype of stroke. Cardiac sources of embolism, active cancers and withdrawal of antithrombotic drugs constituted special risk factors for IHS. A significant proportion of patients were treated with thrombolysis. However, delays in contacting the neurologist excluded a similar proportion of patients from treatment. IHS mortality was high, mostly because of stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
54
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 16 publications
3
54
2
1
Order By: Relevance
“…It has been suggested that ≤15% of IHS cases suitable for thrombolysis were denied treatment because of delays in diagnosis. 6 Public awareness of stroke symptoms has improved in the past decade owing to ongoing public education initiatives 7 ; however, there are limited data examining stroke knowledge among hospital staff. Analysis of US stroke registry data highlighted that evaluation times for IHS remains twice the recommended times, and further investigation of the reasons for these delays in IHS is needed.…”
mentioning
confidence: 99%
“…It has been suggested that ≤15% of IHS cases suitable for thrombolysis were denied treatment because of delays in diagnosis. 6 Public awareness of stroke symptoms has improved in the past decade owing to ongoing public education initiatives 7 ; however, there are limited data examining stroke knowledge among hospital staff. Analysis of US stroke registry data highlighted that evaluation times for IHS remains twice the recommended times, and further investigation of the reasons for these delays in IHS is needed.…”
mentioning
confidence: 99%
“…6,7,18,20 Nearly one quarter of patients with in-hospital stroke are admitted with cardiovascular illness, and many occur postoperatively, particularly after cardiac valve, head and neck, or vascular surgery. 6,8,17,[21][22][23] Multiple concurrent acute illnesses may create conflicting priorities in care and interact in a complex fashion on adherence to disease-specific quality metrics. The presence of interacting acute illnesses may increase the chance that select quality metrics such as the intensity of statin therapy or assessment for rehabilitation needs will be met for patients with in-hospital stroke.…”
mentioning
confidence: 99%
“…[1], [4] Although additional co-morbidities, metabolic or haematological derangements and greater stroke severity in IHS patients are major contributors to poor outcomes, [5] many studies have suggested that delays in recognition, referral, specialist assessment and thrombolysis may also play an important role. [6], [7] Findings suggest that only 25%–50% of in-hospital stroke (IHS) patients are assessed within 3 hours of symptom onset despite already being in a hospital, [6], [7] and 15% of IHS patients may be denied thrombolysis because of these delays. [6] This is important as studies show that the safety and 90 day outcomes of thrombolysis of IHS patients are similar to those who present from outside hospital to emergency departments [8].…”
Section: Introductionmentioning
confidence: 99%